Nanostructured Antimicrobial Peptides: Crucial Steps of Overcoming the Bottleneck for Clinics - Yang, Zhanyi; He, Shiqi; Wu, Hua; Yin, Ting; Wang, Lili; Shan, Anshan (Frontiers in Microbiology, 2021)
The security issue of human health is faced with dispiriting threats from multidrug-resistant bacteria infections induced by the abuse and misuse of antibiotics. Over decades, the antimicrobial peptides (AMPs) hold great promise as a viable alternative to treatment with antibiotics due to their peculiar antimicrobial mechanisms of action, broad-spectrum antimicrobial activity, lower drug residue, and ease of synthesis and modification. However, they universally express a series of disadvantages that hinder their potential application in the biomedical field (e.g., low bioavailability, poor proteases resistance, high cytotoxicity), and extremely waste the abundant resources of AMPs database discovered over the decades. For all these reasons, the nanostructured antimicrobial peptides (Ns-AMPs) based on a variety of nanosystems modification have made up for the deficiencies and pushed the development of novel AMPs-based antimicrobial therapies. In this review, we provide an overview of the advantages of Ns-AMPs in improving therapeutic efficacy and biological stability, reducing side-effects, and gaining the effect of organic targeting and drug controlled-release. Then, the different material categories of Ns-AMPs are described, including inorganic material nanosystems containing AMPs, organic material nanosystems containing AMPs and self-assembled AMPs. Additionally, this review focuses on the Ns-AMPs for the effect of biological activities, with emphasis on antimicrobial activity, biosecurity and biological stability. The “state-of-the-art” antimicrobial modes of Ns-AMPs, including controlled release of AMPs under a specific environment or intrinsic antimicrobial properties of Ns-AMPs, are also explicated. Finally, the perspectives and conclusions of the current research in this field are also summarized.